2011
DOI: 10.1373/clinchem.2011.163824
|View full text |Cite
|
Sign up to set email alerts
|

The Measurement of Platelet-Poor Plasma Serotonin: A Systematic Review of Prior Reports and Recommendations for Improved Analysis

Abstract: BACKGROUND: Recent reports of new and important roles for serotonin (5-hydroxytryptamine, 5-HT) in the periphery have substantially increased interest in measuring peripheral serotonin. Nearly all circulating serotonin is found within platelets and this pool has been assessed by measuring serotonin in whole blood or in platelet-rich plasma. Measurement of the much smaller but potentially critically important pool of human free plasma serotonin in plateletpoor plasma (PPP) has proven much more difficult, with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 108 publications
3
84
0
1
Order By: Relevance
“…Metabolites identified as sensitive to preanalytics should be nominated only carefully as biomarker candidates for disease diagnosis or prognosis, drug efficacy or adverse effects testing and must be thoroughly validated for robustness with respect to preanalytics before publication, product development, or any further application testing. Likewise, reported plasma concentrations of metabolites that are highly affected by preanalytics require careful interpretation, as has been reviewed for serotonin (24 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolites identified as sensitive to preanalytics should be nominated only carefully as biomarker candidates for disease diagnosis or prognosis, drug efficacy or adverse effects testing and must be thoroughly validated for robustness with respect to preanalytics before publication, product development, or any further application testing. Likewise, reported plasma concentrations of metabolites that are highly affected by preanalytics require careful interpretation, as has been reviewed for serotonin (24 ).…”
Section: Discussionmentioning
confidence: 99%
“…3A) and was stable in plasma in this experimental setting. Recent literature has indicated that serotonin in blood is located almost exclusively in platelets (24 ). Therefore, blood processing steps that change platelet metabolism, induce platelet activation, or strive for platelet separation from plasma (platelet-rich plasma vs platelet-poor-plasma) would also be critical for reproducible serotonin analysis from blood (25 ).…”
Section: Metabolomementioning
confidence: 99%
“…Rat free plasma 5-HT has been measured in the low to mid nanogram per milliliter range, largely consistent with those of the human. One to ϳ100 nM concentrations of 5-HT are estimated as platelet free plasma in the human (Kema et al, 2001;Monaghan et al, 2009; estimating a 5-HT molecular weight of 176 g/mol), although Brand and Anderson (2011) question the validity of 5-HT plasma measures in humans given the high variability of 5-HT concentration reported in 101 studies that they compare. The existence of whole-blood monoamine oxidase activity implies that blood, like tissues, has the ability to metabolize 5-HT to a less active substance (Celeda and Artigas, 1993) and keep circulating levels of 5-HT low.…”
Section: -Hydroxytryptamine Synthesis Andmentioning
confidence: 99%
“…The study by Cook and colleagues (1988) reported a substantially lower and more reasonable mean control value of 4.9 nM (*1 ng/ ml). However, even this concentration appears to be above the best estimates of actual mean human PPP 5-HT levels of approximately 1 nM (Beck et al 1993;Brand and Anderson 2011;Anderson 2007). Three of the studies reported lower mean levels of PPP 5-HT in autism compared to controls (Vered et al 2003;Spivak et al 2004;Connors et al 2006), while the fourth reported no difference when compared to family member controls (Cook et al 1988).…”
mentioning
confidence: 77%